2018
DOI: 10.1016/j.celrep.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Enteroviruses Remodel Autophagic Trafficking through Regulation of Host SNARE Proteins to Promote Virus Replication and Cell Exit

Abstract: Summary Enterovirus D68 (EV-D68) is a medically important respiratory plus-strand RNA virus of children that has been linked to acute flaccid myelitis. We have determined that EV-D68 induces autophagic signaling and membrane formation. Autophagy, a homeostatic degradative process that breaks down protein aggregates and damaged organelles, promotes replication of multiple plus-strand viruses. Induction of autophagic signals promotes EV-D68 replication, but the virus inhibits the downstream degradative steps of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
123
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(127 citation statements)
references
References 40 publications
3
123
1
Order By: Relevance
“…Surprisingly, we found that PV mediates instability of the ULK1/2 complex, as the protein levels of all ULK complex members decrease during infection (81). Whether PV induces bona fide autophagy has yet to be determined; PV and other picornaviruses cleave SQSTM1 during infection, confounding our ability to measure autophagic flux (81)(82)(83). PV also does not significantly alter the levels and phosphorylation states of MTOR and AMPK, suggesting that PV-mediated autophagic induction is independent of the MTOR-ULK1/2 signaling axis (81) (Fig.…”
Section: Ulk1/2-independent Autophagy Induction Ulk1/2-independent Aumentioning
confidence: 91%
“…Surprisingly, we found that PV mediates instability of the ULK1/2 complex, as the protein levels of all ULK complex members decrease during infection (81). Whether PV induces bona fide autophagy has yet to be determined; PV and other picornaviruses cleave SQSTM1 during infection, confounding our ability to measure autophagic flux (81)(82)(83). PV also does not significantly alter the levels and phosphorylation states of MTOR and AMPK, suggesting that PV-mediated autophagic induction is independent of the MTOR-ULK1/2 signaling axis (81) (Fig.…”
Section: Ulk1/2-independent Autophagy Induction Ulk1/2-independent Aumentioning
confidence: 91%
“…The cleaved SNAP29, which reportedly regulated formation of autolysosome, facilitated EV-D68 in early infection but was later cleaved. In addition, SNAP47 whose role is unknown in autophagy pathway, was suggested to play a role in regulating EV-D68 induced autophagy and viral release [104]. These findings suggest that EV-D68 benefits from early stage of autophagy and blocks autophagic flux through cleavage of important factors which regulate autolysosome formation, thereby remodeling autophagic trafficking to facilitate viral release.…”
Section: Other Enterovirusesmentioning
confidence: 91%
“…Enterovirus D68 (EV-D68) also benefits from induced autophagy in host cells, as inhibition of autophagy by depletion of E1-like enzyme ATG7 or treatment with bafilomycin A1 undermined viral yield, while induction of autophagy by starvation promoted EV-D68 propagation [104]. Similar to the aforementioned CVB3 infection [89,94], accumulation of GFP-LC3 puncta and cleavage of SNAP29 and SQSTM1 by EV-D68 3C protease were detected in EV-D68 infected Hela cells [104]. The cleaved SNAP29, which reportedly regulated formation of autolysosome, facilitated EV-D68 in early infection but was later cleaved.…”
Section: Other Enterovirusesmentioning
confidence: 99%
“…Autophagy can be modulated to favor viral replication ( Figure 1) [23]. First, viruses can hijack host autophagy pathway to deliver their particles to the replication sites.…”
Section: Propagation Processesmentioning
confidence: 99%